Human calcaneal variation relative to subsistence strategy, activity level, and footwear - Harper, Christine M. (Frontiers in Earth Science, 2023)
Lower limb cortical and trabecular bone varies with human behavior, leading to suggestions that activity level decreases have contributed to a more gracile skeleton. Similar trends are likely present in calcaneal morphology due to its locomotor role during heel strike. Such relationships exist in calcaneal trabecular structure; however, they have yet to be investigated in external morphology. Here entire external calcaneal shape is analyzed among three human populations that vary in subsistence strategy, activity level, and footwear use (n=93) to investigate how calcaneal morphology varies relative to these factors. Calcanei were either surface scanned or micro-CT scanned. Calcaneal external shape was analyzed using a sliding semilandmark analysis with 1007 semilandmarks. Semilandmarks were allowed to slide along tangent vectors or planes to minimize the bending energy of the thin plate spline interpolation function relative to an updated Procrustes average. Final landmark configurations underwent a Generalized Procrustes Analysis. Shape variation of Procrustes coordinates was summarized using principal components analysis (PCA). Procrustes distances between the average calcaneus of each population were calculated, and resampling statistics run to test for significant differences. The three populations exhibit significantly different calcaneal morphologies (p<0.001 for all pairwise comparisons) and separate along the first three PCs (42.11% of variance). Hunter-gatherers have superoinferiorly taller and mediolaterally wider posterior calcanei than sedentary populations. This likely serves as an adaptation for increased load transfer through the posterior calcaneus due to more active lifestyles. This is supported further by variation among the two industrialized populations. The 19 th -20 th century industrialized population exhibits a relatively mediolaterally wider posterior calcaneus than the mid-20 th century-born population, suggesting there has been further gracilization of the calcaneus with increases in sedentary behavior over the last century.